2008
DOI: 10.1002/app.29215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of a new green water‐soluble polymer for proton and metal‐cation sensing

Abstract: A novel water-soluble colored polymer, based on 1,8-naphthalimide, was synthesized through a series of easy reactions with high yields. It emitted green fluorescence both in an aqueous solution and in a solid state. Fluorescence characteristics of the polymer as a function of pH were investigated in aqueous solutions. The polymer solution showed weaker fluorescence in a more acidic medium. When the pH of the solution was higher than 5, stronger fluorescence could be seen with a pK a value of 3.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Because of their strong fluorescence and good photostability, 1,8-naphthalimide derivatives have found application in several areas, such as fluorescent dyes for polymer materials [33,34], laser active media [35,36], fluorescent markers in biology [37], anticancer agents [38] and analgesics [39] in medicine, fluorescence switchers and sensors [40,41], light emitting diodes [42,43], electroluminescent materials [44,45], liquid crystal displays [46,47] and ion probes [48].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their strong fluorescence and good photostability, 1,8-naphthalimide derivatives have found application in several areas, such as fluorescent dyes for polymer materials [33,34], laser active media [35,36], fluorescent markers in biology [37], anticancer agents [38] and analgesics [39] in medicine, fluorescence switchers and sensors [40,41], light emitting diodes [42,43], electroluminescent materials [44,45], liquid crystal displays [46,47] and ion probes [48].…”
Section: Introductionmentioning
confidence: 99%
“…Among those fluorophores reported in the literature, aminophthalimide, which has been used as a fluorescent brightening agent, intracellular biomarker, DNA photocleaver, and electro-luminescent copolymer, is an excellent choice with superb stability and high quantum yield. A series of 1,8-naphthalimide ester analogues with good “‘off–on’” switching of fluorescence upon encountering the correct target have been applied in a number of areas including coloration of polymers, , fluorescent markers in biology, electroluminescent materials, , and also photoinduced electron transfer (PET) sensors. …”
mentioning
confidence: 99%
“…Functional groups, such as amides, ethers, vinyls, and esters, produced materials like nylon, polyester, polyvinyl alcohol and polystyrene [1][2][3][4][5][6][7][8][9][10]. Incorporating azo dyes into polymers give materials that possess nonlinear optical properties, chirotriptic behaviour and can work as optical switches and storage media [8,9,. Over the past decade, our research group has reported the preparation of various classes of organic and organometallic polymers containing azo dyes [33-35, 41-48, 68, 69].…”
Section: Introductionmentioning
confidence: 99%